Pengaruh Gaya Kepemimpinan Intruksional, Loyalitas, Engagement Pegawai, dan Budaya Organisasi Inovatif Terhadap Komitmen Professional Guru Kecamatan Teupah Selatan, Kabupaten Simeulue - Finda Lisna; Hamdi Harmen; Rusdi Rusdi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of instructional leadership and innovative organizational culture on teachers' professional commitment, examine the influence of instructional leadership and innovative organizational culture on teacher loyalty, investigate the mediating role of teacher loyalty, and examine employee engagement as a moderating variable in the relationship between instructional leadership and teachers' professional commitment in Teupah Selatan District, Simeulue Regency. This study employed a quantitative approach using a survey method. The population consisted of 245 Civil Servant (ASN) teachers at the elementary, junior high, and senior high school levels. A total of 150 respondents were selected using the multistage random sampling technique. Data were collected through questionnaires using a Likert scale. The data were analyzed using validity and reliability tests, classical assumption tests, path analysis, the Sobel test, and Moderated Regression Analysis (MRA) with the assistance of SPSS software. The findings indicate that instructional leadership and innovative organizational culture have a positive and significant effect on teachers' professional commitment. Both variables also positively and significantly influence teacher loyalty. Teacher loyalty mediates the effect of instructional leadership on teachers' professional commitment, while employee engagement moderates the relationship between instructional leadership and teachers' professional commitment. These findings suggest that strengthening instructional leadership, fostering an innovative organizational culture, enhancing teacher loyalty, and improving employee engagement can increase teachers' professional commitment.